Scanning Electron Microscopic Study of the Tongue Papillae Formation (Central Asian Journal of Medical Sciences, 2017)
Objectives: To clarify the morphology of the tongue papillae formation and the metabolic characteristics along the papillae distribution in rats. Methods: The experiment was designed as a cross-sectional study and included; a scanning electron and light microscopic examination, connective tissue core analysis, and an enzyme activity test on rat tongue samples of the embryonic (n = 60) and postnatal (n = 12) periods. Results: The primordium of fungiform papillae (FuP) was already formed on embryonic day 15 (E15), and filiform papillae (FiP) was formed on E17. In the postnatal period, the middle and posterior parts of the tongue quickly developed toward the anterior part of the oral cavity. Three types of FiP were found: round, conical and branched. According to the enzyme activity test, all energy, lipid, protein and sugar metabolic enzymes showed significant differences along the tongue parts. Conclusion: No positional difference was found in the morphology of rat tongue papillae during the embryonic period. During the postnatal period, the morphology and enzyme activities of the tongue mucosa displayed differences expressing tongue development and its functional characteristics among the described tongue parts—listed above.